Deciphering the global research trends and significance of moral intelligence via bibliometric analysis - Bagchi, Dipanjan; Srivastava, Akancha; Tushir, Bhawna (Frontiers in Psychology, 2024)
Moral Intelligence (MI) as a concept has gained importance in recent years due to its wide applicability in individual, organizational, and clinical settings or even policy making. The present study employed Bibliometric analysis to understand the emerging topics associated with MI and its global research trend. In this paper the primary aim was i) to explore the temporal and geographic growth trends of the research publication on MI. ii) to identify the most prolific countries, institutions, and authors, working on MI, iii) to identify the most frequent terminologies, iv) to explore research topics and to provide insight into potential collaborations and future directions, and v) to explore the significance of the concept of moral intelligence. Bibliometric analysis was used to understand the emerging topics associated with MI and its global research trend using the SCOPUS database. VOS viewer and R were employed to analyze the result. Through the analysis conducted , the development of the construct over time was analyzed. development over time. Results have shown that Iran and the United States and these two combined account for 53.16% of the total country-wise publications. Switzerland has the highest number of Multi-county publications. Other emerging topics have been highlighted. Implications, future research directions, and scope have been discussed in the paper